Impact of VIDA electronic medical record on teamwork among Peri operative nursing in Saudi Arabia - Amri Yahya Abdullah S. (Journal of Intelligent Decision Making and Information Science, 2026)
Background: The perioperative setting demands high levels of teamwork to ensure patient safety, yet communication breakdowns contribute to over 70% of sentinel events. Traditional paper-based records introduce inefficiencies, such as outdated information and documentation errors, particularly in resource-constrained environments like Jazan Health Cluster, Saudi Arabia. Electronic medical records (EMRs) offer potential solutions by enabling real-time data sharing, but evidence on mobile EMRs in perioperative nursing is limited. This study evaluated the Vida Mobile Software Application, a novel EMR tool, for its impact on teamwork perceptions and patient safety culture. Methods: A quasi-experimental design was employed with 102 healthcare professionals from four hospitals in Jazan Health Cluster. Participants were assigned to control groups (n=52) using paper-based surgical time-out checklists or experimental groups (n=50) implementing the Vida App. Data were collected at baseline (T1), post-intervention (T2), and three-month follow-up (T3) using the TeamSTEPPS Teamwork Perceptions Questionnaire (T-TPQ). Repeated-measures ANOVA, t-tests, and Pearson correlations analyzed changes across six constructs: Team Structure, Leadership, Communication, Mutual Support, Situation Monitoring, and Patient Safety. Results: Experimental groups showed large to massive within-group improvements (partial η² = 0.282–0.719, p < .001), with mean scores rising from 2.41–2.82 at T1 to 4.04–4.95 at T3. Net gains versus controls were 1.58–1.80 points (Cohen's d = 1.58–1.87). Post-intervention correlations with Patient Safety were strong (r = 0.717–0.867). Controls exhibited trivial changes (η² = 0.002–0.079). Conclusion: The Vida App significantly enhances teamwork and patient safety perceptions, offering a scalable digital solution for perioperative care in developing healthcare systems. Implications for Nursing Management: Nurse managers in resource-limited settings, including Saudi public hospitals, can adopt mobile EMR tools like the Vida App to address documentation inefficiencies, reduce communication breakdowns, and foster high-reliability teams. This supports Vision 2030 healthcare digitization goals by overcoming barriers such as digital literacy gaps and infrastructure constraints through user-friendly, offline-capable technology. Managers should prioritize targeted training, policy integration for EMR adoption, ongoing monitoring of teamwork metrics, and leadership support to sustain gains in patient safety and collaborative practice.